A systematic review of small for size syndrome after major hepatectomy and liver transplantation. Issue 4 (April 2020) - Riddiough, Georgina E.; Christophi, Christopher; Jones, Robert M.; Muralidharan, Vijayaragavan; Perini, Marcos V.
Abstract: Background: Major hepatectomy (MH) and particular types of liver transplantation (LT) (reduced size graft, living-donor and split-liver transplantation) lead to a reduction in liver mass. As the portal venous return remains the same it results in a reciprocal and proportionate rise in portal venous pressure potentially resulting in small for size syndrome (SFSS). The aim of this study was to review the incidence, diagnosis and management of SFSS amongst recipients of LT and MH. Methods: A systematic review was performed in accordance with the 2010 Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. The following terms were used to search PubMed, Embase and Cochrane Library in July 2019: ("major hepatectomy" or "liver resection" or "liver transplantation") AND ("small for size syndrome" or "post hepatectomy liver failure"). The primary outcome was a diagnosis of SFSS. Results: Twenty-four articles met the inclusion criteria and could be included in this review. In total 2728 patients were included of whom 316 (12%) patients met criteria for SFSS or post hepatectomy liver failure (PHLF). Of these, 31 (10%) fulfilled criteria for PHLF following MH. 8 of these patients developed intractable ascites alongside elevated portal venous pressure following MH indicative of SFSS. Conclusion: SFSS is under-recognised following major hepatectomy and should be considered as an underlying cause of PHLF. Surgical and pharmacological therapies are available to reduce portal congestion and reverse SFSS.